Paraduodenal Pancreatitis: An Italian Experience on 112 Patients - De Pretis, Niccolò; Amodio, Antonio; Casetti, Luca; Granato, Anna; De Marchi, Giulia; Gabbrielli, Armando; Vantini, Italo; Bassi, Claudio; Benini, Luigi; Frulloni, Luca (JOP. Journal of the Pancreas, 2013)
Context Paraduodenal pancreatitis (PP) is a special form of chronic pancreatitis, called also groove pancreatitis or cystic dystrophy of the duodenal wall, defined on surgical specimens. Characteristic findings at CT, MR and EUS has been published. Objective to evaluate the clinical and radiological features of PP, and the clinical outcome in a mixed clinical and surgical series. Methods All patients with a final diagnosis of PP in gastroenterology unit and surgical department have been enrolled. Clinical, radiological and pathological data have been collected. The diagnosis was based on surgical specimens in operated patients and on imaging in non operated patients. Results We studied 112 patients (108 males, 4 females; mean age 41.4±10 years), 96.4% of them were drinkers (mean daily alcohol intake: 129.3±65.4 g) and 97.3% smokers (29.2±13.6 cigarettes/day). The clinical onset was acute pancreatitis in 70 patients (63%) and continuous pain in 42 (38%). Other symptoms at onset were vomiting (42 patients, 38%), weight loss (26 patients, 23%) and jaundice (13 patients, 12%). Cystic variant was diagnosed in 79 patients (70%) and solid in 33 (30%). Pure form involving only the groove area was observed in 22 patients (20%) and diffuse form involving all pancreas in 90 (80%). Pancreatic calcifications were diagnosed in 68 patients (61%). Seventy-four patients (70%) underwent surgery, resective in 57 and derivative in 17. The indication for surgery were pain (67 patients, 86%), suspicion of cancer (5 patients, 6%) and duodenal obstruction (6 patients, 8%). Mean follow-up time was 5±7 years. Diabetes was diagnosed in 28% and steatorrhea in 25%. Ten patients (9%) died. Conclusion The clinical profile of PP are middle age males, heavy drinkers and smokers, with painful pancreatitis, associated with vomiting and weight loss. Resective surgery is the treatment of choice in our institution.